Super-hydrophilic wick, preparation method of super-hydrophilic wick, vapor chamber and preparation method of vapor chamber
By designing a super hydrophilic liquid absorbing core with concave characteristics in the heat-homogenic plate, and using the electrodeposition process to enhance the capillary effect, the problem of insufficient performance of the liquid absorbing core of the traditional heat-homogenic plate is solved, and efficient liquid circulation and heat conduction are achieved. Improved heat dissipation performance.
Patent Information
- Application Number
- CN202411318286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The liquid absorbent core of the traditional heat-smooth plate is insufficient and has limited hydrophilicity. It is impossible to quickly and effectively transport the liquid working fluid back to the evaporation section under high heat flow density, resulting in low heat dissipation efficiency and a single microstructure design, which is unable to adapt to different thermal loads. and application scenarios.
Design a super hydrophilic liquid absorbent core, which includes a zero-order structure, a primary-order structure and a secondary structure. The primary-order structure is a rod-shaped or pointed conical microstructure arranged side by side on the surface of the zero-order structure, and the secondary structure has a round and blunt shape. The microstructure is wrapped around the top of the primary structure, forming an integral concave feature, and is prepared by an electrodeposition process to enhance capillary action and hydrophilicity.
It significantly improves the circulation efficiency and heat conduction effect of working liquids, improves the heat dissipation performance of the heat-smoothing plate. It is suitable for heat-smoothing plates of various sizes and shapes, and has a wide range of application prospects.
Smart Images

Figure CN119212308A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a vapor chamber radiator manufacturing technology, and in particular to a super-hydrophilic liquid wick and a preparation method thereof, a vapor chamber and a preparation method thereof. Background Art
[0002] With the continuous improvement of the performance of electronic equipment, especially the rapid development of high-performance computing, big data processing, 5G communication technology, artificial intelligence and other fields, the heat flux density of electronic devices continues to increase, which puts higher requirements on heat dissipation technology.
[0003] As a highly efficient phase-change heat dissipation device, the vapor chamber achieves rapid heat transfer and uniform distribution through the evaporation and condensation process of the internal working fluid, and has been widely used in the heat dissipation system of high-end electronic equipment. At present, the high-efficiency heat transfer characteristics of phase-change heat and mass transfer inside the vapor chamber can achieve lower thermal resistance and higher temperature uniformity. However, with the trend of increasingly thin vapor chamber thickness, traditional vapor chambers still have the following limitations:
[0004] 1) Insufficient performance of the wick: The traditional wick has a simple structure and limited capillary force, making it difficult to quickly and effectively transport the liquid working medium back to the evaporation section under high heat flux density;
[0005] 2) Limited hydrophilicity: The hydrophilicity of the wick directly affects the reflux rate of the working fluid. The insufficient hydrophilicity of traditional materials limits the heat dissipation efficiency of the vapor chamber.
[0006] 3) Single microstructure design: The existing microstructure design is usually single and cannot be optimized for different heat loads and application scenarios, which affects the adaptability and performance of the vapor chamber.
[0007] In order to solve the above problems, how to optimize the microstructure and surface properties of the wick through design, improve the reflux speed of the working fluid and the heat dissipation efficiency of the heat spreader has become the most critical factor in providing a more efficient and reliable heat dissipation solution for high-performance electronic devices.
[0008] The strength of the capillary force determines the reflow speed and heat dissipation efficiency of the heat spreader.
[0009] Capillary force is caused by the surface tension and contact angle of the liquid, which can push the liquid up or down in the capillary. The height of the liquid rising or falling in the capillary phenomenon can be calculated by the following formula:
[0010]
[0011] Where: h is the height that the liquid rises or falls in the capillary; γ is the surface tension of the liquid; θ is the contact angle; ρ is the density of the liquid; g is the acceleration due to gravity; and r is the radius of the capillary.
[0012] From the above formula, we can see that the smaller the contact angle, the greater the rise height of the liquid in the capillary, which generally means that the liquid has better wettability to the solid surface. On the contrary, if the contact angle is close to 180°, the rise height of the liquid in the capillary will be small or even decrease, indicating that the liquid has poor wettability to the solid surface.
[0013] Both contact angle and wettability are affected by factors such as liquid properties (such as surface tension), solid properties (such as surface energy, roughness) and environmental conditions (such as temperature, pressure). From the above formula, it can be deduced that if the surface has a large number of concave microstructures, it is conducive to the complete wetting of the liquid in the concave area, thereby improving the effect of capillary action. However, it is very difficult to form a large number of regular concave areas on the inner surface of the heat spreader from the perspective of processing technology. Therefore, novel and effective large-scale preparation of microstructures has important technical significance.
[0014] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0015] In order to make up for the deficiencies of the prior art, the present invention provides a super-hydrophilic liquid absorbent core and a preparation method thereof, a heat spreader and a preparation method thereof.
[0016] In order to achieve the above objectives, this application adopts the following technical solutions:
[0017] In the first aspect, a super hydrophilic liquid-absorbing core is provided, which includes a zero-order structure, a primary structure and a secondary structure, wherein the primary structure is a rod-shaped or cone-shaped microstructure and is arranged on the surface of the zero-order structure, the secondary structure is a microstructure with a blunt shape and wraps the top of the primary structure, and the diameter of the secondary structure is larger than the diameter of the top of the primary structure, so that the overall structure formed by the secondary structure and the primary structure has a concave feature.
[0018] In a second aspect, a method for preparing the super hydrophilic liquid absorbent core according to the first aspect is provided, comprising the following steps:
[0019] (1) First deposition: using the material of the primary structure as a deposition material and the zero-order structure as a working electrode, depositing a primary structure having a rod-shaped or pointed cone-shaped microstructure on the surface of the zero-order structure;
[0020] (2) Second deposition: Using the sample obtained by the first deposition as the working electrode, electro-deposit the secondary structure with a microstructure having a rounded shape on the top of the primary structure.
[0021] In a third aspect, a heat spreader is provided, which includes an upper shell plate, a lower shell plate, an upper liquid absorbent core, a lower liquid absorbent core and an injection hole; the upper shell plate and the lower shell plate are connected to each other to form a closed steam chamber, the injection hole is connected to the steam chamber, the steam chamber is filled with working liquid through the injection hole, the upper liquid absorbent core is arranged in the inner surface groove of the upper shell plate, the lower liquid absorbent core is arranged in the inner surface groove of the lower shell plate, and the upper liquid absorbent core and / or the lower liquid absorbent core are the super hydrophilic liquid absorbent core described in the first aspect.
[0022] In a fourth aspect, a method for preparing the vapor chamber according to the third aspect is provided, comprising the following steps:
[0023] (1) preparing an upper shell plate and a lower shell plate having grooves on the inner surface;
[0024] (2) forming an upper liquid wick and a lower liquid wick in the inner surface grooves of the upper shell plate and the lower shell plate respectively;
[0025] (3) connecting the upper shell plate and the lower shell plate to form a closed steam chamber and evacuating the chamber; preferably, the vacuum degree in the steam chamber is maintained at 0.01-5000 Pa, preferably, the vacuum degree is 0.1-1000 Pa;
[0026] (4) Inject working liquid through the liquid injection hole and perform sealing and packaging to obtain the heat spreader.
[0027] The present invention has beneficial effects: the super-hydrophilic liquid-absorbing core of the present invention has super-strong hydrophilicity and capillary action characteristics. After being applied to a heat spreader, its rod-shaped or pointed cone-shaped primary structure is conducive to the adsorption and rise of the working liquid. The rounded and blunt shape of the secondary structure and the concave characteristics of the overall structure significantly enhance the capillary action and promote the circulation of the working liquid, thereby achieving effective circulation of the working liquid and efficient heat conduction. The heat spreader is used for heat dissipation of electronic equipment and can improve the heat transfer effect. The present invention can be widely used in heat spreader radiators of various sizes and shapes, and has broad application prospects and commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the overall structure of a vapor chamber with a super-hydrophilic liquid wick in an embodiment of the present invention;
[0029] Figure 2 Schematic diagram of the structure of the super hydrophilic liquid absorbent core (foam copper type) in Example 1 of the present invention (wherein, Figure 2 The right figure is an enlarged schematic diagram of part A of the left figure);
[0030] Figure 3 Schematic diagram of the structure of the super hydrophilic liquid absorbent core (micro groove type) in Example 2 of the present invention (wherein, Figure 3The lower figure is an enlarged schematic diagram of part B of the upper figure);
[0031] Figure 4 This is a schematic diagram of a pointed cone-shaped primary structure obtained by the first electrodeposition in an embodiment of the present invention;
[0032] Figure 5 It is a schematic diagram of the overall structure of the secondary structure with a rounded appearance obtained by the second electrodeposition in an embodiment of the present invention and the "mushroom" shape formed together with the primary structure;
[0033] Figure 6 A cross-sectional view of a "matchstick" or "mushroom" shaped overall structure in an embodiment of the present invention, highlighting the concave features formed by the primary structure and the secondary structure;
[0034] Figure 7 This is a scanning electron microscope image of the liquid-absorbing core with a "mushroom"-shaped microstructure in Example 3 of the present invention;
[0035] Figure 8 This is a schematic diagram of a rod-shaped primary structure obtained by the first electrodeposition in other embodiments of the present invention;
[0036] Fig. 9 A schematic diagram of the overall structure of a secondary structure with a rounded appearance obtained by the second electrodeposition in other embodiments of the present invention and a "matchstick" shape formed together with the primary structure;
[0037] Fig.10 It is a cross-sectional view of a "matchstick"-shaped overall structure in other embodiments of the present invention, highlighting the concave features formed by the primary structure and the secondary structure. DETAILED DESCRIPTION
[0038] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other.
[0039] An embodiment of the present invention provides a super-hydrophilic liquid-absorbing core, which includes a zero-order structure, a primary structure and a secondary structure, wherein the primary structure is a rod-shaped or cone-shaped microstructure arranged on the surface of the zero-order structure, the secondary structure is a microstructure with a blunt shape and wraps the top of the primary structure, and the diameter of the secondary structure is greater than the diameter of the top of the primary structure, so that the overall structure formed by the secondary structure and the primary structure has a concave feature.
[0040] In a preferred embodiment, the top of each primary structure corresponds to a secondary structure, and the overall structural array formed by the primary structure and the secondary structure is randomly or periodically arranged on the surface of the zero-order structure, wherein the concave features on each overall structure (the connection transition between the secondary structure and the primary structure is concave) have an enhanced capillary adsorption effect.
[0041] In a preferred embodiment, the aspect ratio of the primary structure is 1:1-30:1, preferably, the aspect ratio of the primary structure is 3:1 to 8:1; the length of the primary structure is 1nm-100μm, preferably, the length of the primary structure is 500nm-10μm.
[0042] In a preferred embodiment, the diameter of the secondary structure is 1 nm-150 μm, preferably, the diameter of the secondary structure is 150 nm-1.5 μm.
[0043] In a preferred embodiment, the overall structure formed by the secondary structure and the primary structure includes but is not limited to a "matchstick" shape or a "mushroom" shape.
[0044] In a preferred embodiment, the concave angle of the concave feature is between 15-150°, and the diameter of the secondary structure can be controlled by controlling the parameters of the electrodeposition process, thereby controlling the concave angle.
[0045] In a preferred embodiment, the distance between two adjacent primary structures is 1 nm-100 μm, and preferably, the distance between two adjacent primary structures is 0.3 μm-10 μm.
[0046] In a preferred embodiment, the zero-order structure is one of the inner surface groove of the shell plate of the heat spreader when the super hydrophilic wick is used in the heat spreader, the surface of the micro-groove wick structure, the surface of the foam metal wick structure, and the surface of the metal mesh wick structure.
[0047] In a preferred embodiment, the main production method of the zero-order structure includes micro-nanoscale processing methods such as sintering, cutting, and etching, etc. The material of the zero-order structure is a metal material with good electrical conductivity (such as non-ferrous metals such as copper, aluminum, nickel, and their alloy materials), the material of the primary structure is a metal material with good electrical conductivity (such as non-ferrous metals such as copper, nickel, and other non-ferrous metals), and the material of the secondary structure is a metal with poor solubility with the material of the primary structure (preferably a transition metal with excellent capillary properties, such as tungsten, molybdenum or other transition metals). Preferably, the material of the primary structure is different from the material of the secondary structure; preferably, the material of the primary structure is copper or nickel, and the material of the secondary structure is molybdenum or tungsten; more preferably, the material of the primary structure is nickel, and the material of the secondary structure is molybdenum.
[0048] The specific embodiment of the present invention also provides a method for preparing the super hydrophilic liquid absorbent core, which comprises the following steps:
[0049] (1) First deposition: using the material of the primary structure as the deposition material and the zero-order structure as the working electrode, depositing on the surface of the zero-order structure a primary structure having a rod-shaped or cone-shaped microstructure; for example, electrodeposition is performed in a two-electrode electrochemical cell, using copper or nickel as the deposition material, using the zero-order structure as the working electrode, using a zero-order structure of the same size placed in parallel with the counter electrode, preparing an electrolyte of a certain concentration and adjusting the pH value with an acid or alkaline solution, and performing electrodeposition under certain electrodeposition parameters. After a certain deposition period, a primary structure having a rod-shaped or cone-shaped geometric feature can be grown on the surface of the zero-order structure. Subsequently, the sample is removed from the electrolyte, rinsed, and dried naturally.
[0050] (2) Second deposition: Using the sample obtained by the first deposition as the working electrode, electro-deposit the secondary structure with a microstructure having a rounded shape on the top of the primary structure. For example, a layer of metal with poor miscibility with the primary structure is continuously electro-deposited on top of the primary structure obtained by the first electro-deposition. Specifically, the sample in the above step (1) is electro-deposited in a two-electrode electrochemical cell, using the sample as the working electrode, using a sample of the same size placed in parallel as the counter electrode, preparing an electrolyte of a certain concentration and adjusting the pH value with an acid or alkaline solution, and electro-depositing under certain electro-deposition parameters. After a certain deposition time, a secondary structure with a rounded shape is obtained on the top of the primary structure. The sample is taken out of the electrolyte, rinsed, dried naturally, and observed by means of a scanning electron microscope to ensure that the microstructure obtained by the secondary electro-deposition forms a concave geometric feature with the primary microstructure to enhance the capillary action.
[0051] In a preferred embodiment, the process conditions of the first deposition and the second deposition are independently:
[0052] Current density is 0.5-300mA·cm -2 Preferably, the current density is 5-150 mA·cm -2 ;
[0053] The electrodeposition time is 1s-90min, preferably, the electrodeposition time is 30s-30min;
[0054] The electrodeposition temperature is 0-150°C, preferably, the electrodeposition temperature is 25-100°C.
[0055] By controlling the process conditions of electrodeposition, the length, diameter of the primary structure, the diameter of the secondary structure, the concave angle, etc. can be controlled to adapt to different heat sink designs and performance requirements.
[0056] A specific embodiment of the present invention also provides a heat spreader, which includes an upper shell plate, a lower shell plate, an upper liquid absorbent core, a lower liquid absorbent core and an injection hole; the upper shell plate and the lower shell plate are connected to each other to form a closed steam chamber, the injection hole is connected to the steam chamber, the steam chamber is filled with working liquid through the injection hole, the upper liquid absorbent core is arranged in the inner surface groove of the upper shell plate, the lower liquid absorbent core is arranged in the inner surface groove of the lower shell plate, and the upper liquid absorbent core and / or the lower liquid absorbent core are the super hydrophilic liquid absorbent core.
[0057] In a preferred embodiment, the upper shell plate and the lower shell plate are made of a material with good thermal conductivity (such as metals such as copper, aluminum, and alloy materials thereof, or non-metallic materials).
[0058] The specific embodiment of the present invention also provides a method for preparing the vapor chamber, which comprises the following steps:
[0059] (1) preparing an upper shell plate and a lower shell plate with grooves on the inner surface; for example, the upper shell plate and the lower shell plate are made of materials with good thermal conductivity such as copper sheets or aluminum sheets through stamping, etching or CNC, laser processing and other processes to form a structure with a central groove and edge protrusions.
[0060] (2) forming an upper liquid wick and a lower liquid wick in the inner surface grooves of the upper shell plate and the lower shell plate respectively;
[0061] (3) connecting the upper shell plate and the lower shell plate to form a closed steam chamber and evacuating the chamber; preferably, the vacuum degree in the steam chamber is maintained at 0.01-5000 Pa, preferably, the vacuum degree is 0.1-1000 Pa;
[0062] (4) Inject working liquid through the liquid injection hole and perform sealing and packaging to obtain the heat spreader.
[0063] The super-hydrophilic liquid-absorbing core in the specific embodiment of the present invention has good capillary phenomenon, can realize liquid medium phase change and rapid circulation, and further, can form a microstructure (primary structure + secondary structure) with excellent capillary action characteristics on the surface of the zero-order structure by precisely controlling the electrodeposition process (for example, the shape and size of the microstructure can be customized by precisely controlling the electrodeposition process to meet different heat sink designs and performance requirements) to improve the heat conduction efficiency of the heat spreader. The specific embodiments of the present invention are further described below.
[0064] Example 1
[0065] A heat spreader with a super hydrophilic absorbent core (foam metal type) with a thickness of 3.4 mm, such as Figure 1 As shown, the preparation of the vapor chamber includes the following steps:
[0066] (1) The upper shell plate 1 and the lower shell plate 3 are both made of copper sheets with a thickness of 0.8 mm, and are both stamped to obtain a groove 9 (edge protrusion) on the inner surface. The height of the chamber formed by the upper shell plate 1 and the lower shell plate 3 when combined is about 1.8 mm.
[0067] (2) A commercially available copper foam 20 of about 0.3 mm in diameter (as the zero-order structure of the wick) is selected and cut into a shape consistent with the size of the groove 9. The copper foam 20 is ultrasonically treated in a 10 wt % HCl solution for 10 minutes to remove the oxide layer on the surface, and then rinsed with water and ethanol and dried in air.
[0068] (3) The first electrodeposition was carried out in a two-electrode electrochemical cell: the copper foam 20 in step (2) was used as the working electrode, and the copper foam of the same size was placed in parallel as the counter electrode. The electrolyte was prepared with deionized water (about 18.0 MΩ·cm at 25°C) and the concentrations of 1.05 M NiCl2·6H2O, 0.813 M HBO3 and 2.325 M NH4Cl. The pH value was adjusted to 4.0 with 10 wt% HCl solution. At 25 mA·cm -2 Under the direct current power supply, the electrodeposition was carried out at 65℃, such as Figure 4 As shown, after 18 minutes of deposition, a nickel cone array 51 (primary structure) can be obtained on the copper foam 20. The copper foam sample with nickel cones deposited thereon is taken out from the electrolyte, thoroughly rinsed with water and ethanol, and dried naturally. In this example, a dense array of nickel cones is formed on the surface of the copper foam 20 after 18 minutes of electrodeposition, with a height of about 1 μm, and the distance between the centers of two adjacent nickel cone primary microstructures is about 500 nm, as shown in FIG. Figure 2 shown.
[0069] (4) Perform secondary electrodeposition. Electrodeposit the copper foam sample on which the nickel cone is deposited in step (3) above in a two-electrode electrochemical cell. Use the copper foam as the working electrode and a copper foam of the same size placed in parallel as the counter electrode. Use deionized water (about 18.0 M·cm at 25° C.) to prepare an electrolyte with a concentration of 3.3 g sodium citrate, 2.96 g nickel sulfate dihydrate, and 1.8 g sodium molybdate dihydrate. Use a 10 wt % NH4OH solution to adjust the pH to 10.5. At 100 mA·cm -2 The electrodeposition was carried out at 35°C under a DC power supply. After 80 seconds of deposition, a molybdenum ball 52 (secondary structure) with a rounded shape was obtained at the top of the nickel cone. The sample was taken out of the electrolyte, thoroughly rinsed with water and ethanol, and dried naturally. After 60 seconds of electrodeposition, a uniform molybdenum ball 52 with a diameter of about 400 nm was formed on the top of the nickel cone 51 array. The nickel cone 51 (primary structure) and the molybdenum ball 52 (secondary structure) together formed a round mushroom-shaped microstructure 5, as shown in FIG. Figure 5 shown.
[0070] (5) The above-mentioned foam copper with the mushroom-shaped microstructure 5 is welded as the liquid wick 2 in the grooves 9 of the upper shell plate 1 and the lower shell plate 3, as shown in FIG. Figure 1 shown.
[0071] (6) The prepared upper shell plate and lower shell plate with super hydrophilic absorbent core are covered to form a whole and evacuated, and the vacuum degree inside the cavity is maintained at 1 Pa.
[0072] (7) Deionized water or other working liquid is injected into the cavity through the liquid injection hole 4, and finally a sealing and packaging process is performed to obtain a heat spreader.
[0073] The above-mentioned heat spreader with super hydrophilic liquid absorbent core has the following characteristics: the primary structure of the liquid absorbent core is a microstructure with a pointed cone-shaped geometric feature, which is arranged on the surface of the zero-level structure of the foam copper; the secondary structure is a microstructure with a rounded appearance, which is wrapped above the primary structure; the microstructure 5 obtained by secondary electrodeposition has a concave geometric feature 8 (with a concave angle 81, and the concave angle is about 92°) under the "mushroom head", such as Figure 6 As shown in the figure, the primary structure and the secondary structure together form an overall mushroom shape and are randomly arranged on the surface of the zero-level structure of the copper foam, and the spacing between each mushroom-shaped microstructure is about 500nm. The two-level microstructure formed in this embodiment provides a large number of concave microstructures for the heat spreader, which improves the capillary effect and thus improves the heat transfer effect.
[0074] Example 2
[0075] The preparation of a heat spreader (micro-groove type) with a thickness of 2.2 mm and a super hydrophilic wick comprises the following steps:
[0076] (1) The upper shell plate 1 and the lower shell plate 3 are both made of copper sheets with a thickness of 0.5 mm. The grooves (edge protrusions) on the inner surface are obtained by stamping. The height of the chamber formed by the upper shell plate 1 and the lower shell plate 3 together is about 1.2 mm.
[0077] (2) Figure 3 The micro-groove 60 structure shown (as a zero-level structure) is etched into the grooves of the upper shell plate 1 and the lower shell plate 3, respectively, and the upper shell plate or the lower shell plate with the micro-groove structure is subjected to preliminary pretreatment such as cleaning.
[0078] (3) The upper and lower shell plates in step (2) were placed in a 10 wt % HCl solution for ultrasonic treatment for 5 minutes to remove the oxide layer on the surface, and then rinsed with water and ethanol and dried in air.
[0079] (4) Perform the first electrodeposition in a two-electrode electrochemical cell: Use the upper shell plate in step (3) as the working electrode, use a shell plate of the same size placed in parallel as the counter electrode, use deionized water (about 18.0 MΩ·cm at 25°C) to prepare the electrolyte at a concentration of 0.924 M NiCl2·6H2O, 0.715 M HBO3 and 2.046 M NH4Cl, and adjust the pH value to 4.0 with 10 wt% HCl and 10 wt% NH4OH solution. -2 Under a DC power supply, the electrodeposition was carried out at 60°C. After 15 minutes of deposition, a nickel cone 51 array can be obtained on the surface of the micro-groove 60, such as Figure 4 As shown. The upper shell plate sample was taken out from the electrolyte, rinsed thoroughly with water and ethanol, and dried naturally. After 15 minutes of electrodeposition, a dense array of nickel cones was formed on the surface of the micro-grooves 60, with a height of about 900nm and a distance between the centers of two adjacent nickel cones of about 450nm. Similarly, the lower shell plate in the above step (3) was used as the working electrode, and nickel cones 51 were deposited on the lower shell plate.
[0080] (5) Perform secondary electrodeposition, and electrodeposit the upper shell plate sample in step (4) in a two-electrode electrochemical cell: use the upper shell plate in step (4) as the working electrode, and use a shell plate of the same size placed in parallel as the counter electrode. Use deionized water (about 18.0 MΩ·cm at 25°C) to prepare the electrolyte at a concentration of 2.9 g sodium citrate, 2.6 g nickel sulfate dihydrate, and 1.58 g sodium molybdate dihydrate. Use 10 wt% NH4OH solution to adjust the pH to 10.5, and charge and discharge at 80 mA·cm -2 The electrodeposition was carried out at 35°C under a DC power supply. After 60 seconds of deposition, a molybdenum ball 52 with a rounded shape was formed at the top of the nickel cone 51. The sample with the secondary structure was taken out from the electrolyte, thoroughly rinsed with water and ethanol, and dried naturally. After 60 seconds of electrodeposition, uniform molybdenum balls 52 with a diameter of about 300 nm were formed at the top of the nickel cone 51 array. The nickel cone (primary structure) and the molybdenum ball 52 (secondary structure) together formed a round mushroom-shaped microstructure 5, as shown in FIG. Figure 5 Similarly, the lower shell plate in the above step (4) is used as the working electrode, and molybdenum beads 52 are deposited on the nickel cone 51 on the lower shell plate.
[0081] (6) The prepared upper shell plate and lower shell plate with super hydrophilic absorbent core are covered to form a whole and evacuated, and the vacuum degree inside the cavity is maintained at 30 Pa.
[0082] (7) Working liquid is injected into the cavity through the liquid injection hole 4, and finally a sealing and packaging process is performed to obtain a heat spreader.
[0083] The above-mentioned heat spreader with super hydrophilic liquid absorbent core has the following characteristics: the primary structure of the liquid absorbent core is a microstructure with a pointed cone-shaped geometric feature, which is randomly arranged on the surface of the grooved zero-order structure; the secondary structure is a microstructure with a rounded appearance, which is wrapped above the primary structure; the microstructure obtained by secondary electrodeposition has a concave geometric feature 8 (with a concave angle 81, and the concave angle is about 93°) under the "mushroom head", such as Figure 6 As shown in the figure, the primary structure and the secondary structure together form an overall mushroom shape and are randomly arranged on the surface of the zero-level structure, and the spacing between each mushroom-shaped microstructure is about 450nm. The two-level microstructure formed in this embodiment provides a large number of concave microstructures for the heat spreader, which improves the capillary effect and thus improves the heat transfer effect.
[0084] Example 3
[0085] The preparation of an ultra-thin vapor chamber with a thickness of 0.6 mm and a super-hydrophilic liquid wick comprises the following steps:
[0086] (1) The upper shell plate 1 and the lower shell plate 3 are both made of copper sheets with a thickness of 0.15 mm. The grooves (edge protrusions) on the inner surface are obtained by stamping. The height of the chamber formed by the upper shell plate 1 and the lower shell plate 3 together is about 0.3 mm.
[0087] (2) The upper shell plate and the lower shell plate with grooves are pre-treated by cleaning.
[0088] (3) The upper and lower shell plates in step (2) were placed in a 10 wt % HCl solution for ultrasonic treatment for 5 minutes to remove the oxide layer on the surface, and then rinsed with water and ethanol and dried in air.
[0089] (4) The first electrodeposition was carried out in a two-electrode electrochemical cell. The upper shell plate in (3) was used as the working electrode, and a shell plate of the same size placed in parallel was used as the counter electrode. Deionized water (about 18.0 MΩ·cm at 25°C) was used to prepare the electrolyte at a concentration of 0.84 M NiCl2·6H2O, 0.65 M HBO3, and 1.86 M NH4Cl. The pH value was adjusted to 4.0 with 10 wt% HCl and 10 wt% NH4OH solution. At 20 mA·cm -2 Under a DC power supply, the electrodeposition was carried out at 60°C. After 13 minutes of deposition, a nickel cone 51 array was obtained on the surface of the groove 9, as shown in FIG. Figure 4 As shown. The upper shell plate sample was removed from the electrolyte, rinsed thoroughly with water and ethanol, and dried naturally. After 13 minutes of electrodeposition, a dense array of nickel cones 51 was formed on the surface of the groove 9, with a height of about 800nm, and the distance between the centers of the primary microstructures of two adjacent nickel cones was about 350nm. Similarly, the lower shell plate in the above step (3) was used as the working electrode, and nickel cones 51 were deposited on the lower shell plate.
[0090] (5) Perform secondary electrodeposition, and electrodeposit the upper shell plate sample in step (4) in a two-electrode electrochemical cell: use the upper shell plate in step (4) as the working electrode, and use a shell plate of the same size placed in parallel as the counter electrode. Use deionized water (about 18.0 MΩ·cm at 25°C) to prepare an electrolyte with a concentration of 2.64 g sodium citrate, 2.37 g nickel sulfate dihydrate, and 1.44 g sodium molybdate dihydrate. Use 10 wt% NH4OH solution to adjust the pH to 10.5, and charge and discharge at 80 mA·cm -2 The electrodeposition was carried out at 35°C under a DC power supply. After 50 seconds of deposition, a molybdenum ball 52 with a rounded shape can be obtained at the top of the nickel cone 51. The sample was taken out of the electrolyte, thoroughly rinsed with water and ethanol, and dried naturally. After 40 seconds of electrodeposition, uniform molybdenum balls 52 with a diameter of about 200 nm were formed at the top of the array of nickel cones 51. The nickel cones (primary structure) and the molybdenum balls 52 (secondary structure) together formed a round mushroom-shaped microstructure 5, as shown in FIG. Figure 5 and Figure 7 Similarly, the lower shell plate in the above step (4) is used as the working electrode, and molybdenum beads 52 are deposited on the nickel cone 51 on the lower shell plate.
[0091] (6) The prepared upper shell plate and lower shell plate with super hydrophilic absorbent core are covered to form a whole and evacuated, and the vacuum degree inside the cavity is maintained at 50 Pa.
[0092] (7) Working liquid is injected into the cavity through the liquid injection hole 4, and finally a sealing and packaging process is performed to obtain a heat spreader.
[0093] The above-mentioned heat spreader with super hydrophilic liquid absorbent core has the following characteristics: the primary structure of the liquid absorbent core is a microstructure with a pointed cone-shaped geometric feature, which is arranged on the inner groove surface of the upper and lower shell plates (zero-order structure surface), and the secondary structure is a microstructure with a blunt appearance, which is wrapped above the primary structure. The microstructure obtained by secondary electrodeposition has a concave geometric feature 8 (with a concave angle 81, and the concave angle is about 94°) below the "mushroom head", such as Figure 6 As shown in the figure, the primary structure and the secondary structure together form an overall mushroom shape and are randomly arranged on the surface of the zero-level structure, and the spacing between each mushroom-shaped microstructure is about 350nm. The two-level microstructure formed in this embodiment provides a large number of concave microstructures for the heat spreader, which improves the capillary effect and thus improves the heat transfer effect.
[0094] In other embodiments, a rod-shaped primary structure 71 can be deposited on the surface of the zero-order structure 10 by a conventional nanowire preparation method in the art, and then a secondary deposition is performed by the same method as in the above embodiments 1-3 to deposit a blunt-shaped secondary structure 72 on the top of the rod-shaped primary structure 71, such as Figure 8-10 As shown, Figure 8 is a schematic diagram of a rod-shaped primary structure 71 obtained by first electrodeposition on the surface of the zero-order structure 10; Fig. 9 A schematic diagram of a secondary structure 72 with a rounded appearance obtained by the second electrodeposition and a "matchstick"-shaped overall structure 7 formed together with the primary structure 71; Fig.10 The cross-sectional view of the "matchstick" shaped integral structure 7 highlights the concave feature 8 with a concave corner 81 formed by the primary structure 71 and the secondary structure 72. The heat spreader of the liquid wick using the "matchstick" shaped integral structure 7 can also greatly improve the heat transfer effect.
[0095] The primary structure of the vapor chamber in the embodiment of the present invention in its liquid wick can effectively improve the liquid flow efficiency, and the finer secondary structure (hydrophilic capillary microstructure) can provide excellent capillary action. The vapor chamber with a super hydrophilic liquid wick can greatly improve the heat transfer effect of the radiator. The method of the present invention is suitable for the preparation of vapor chambers of all sizes (including standard vapor chambers and ultra-thin vapor chambers).
[0096] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A super hydrophilic liquid absorbent core, characterized in that: It includes a zero-order structure, a primary structure and a secondary structure. The primary structure is a rod-shaped or cone-shaped microstructure arranged on the surface of the zero-order structure. The secondary structure is a microstructure with a blunt shape and wraps the top of the primary structure. The diameter of the secondary structure is larger than the diameter of the top of the primary structure, so that the overall structure formed by the secondary structure and the primary structure has a concave feature.
2. The super hydrophilic absorbent core according to claim 1, wherein: The aspect ratio of the primary structure is 1:1-30:1, preferably, the aspect ratio of the primary structure is 3:1 to 8:1; the length of the primary structure is 1nm-100μm, preferably, the length of the primary structure is 500nm-10μm.
3. The super hydrophilic absorbent core according to claim 1, wherein: The diameter of the secondary structure is 1 nm-150 μm, preferably, the diameter of the secondary structure is 150 nm-1.5 μm; The overall structure formed by the secondary structure and the primary structure is in the shape of a "matchstick" or a "mushroom".
4. The super hydrophilic absorbent core according to claim 1, wherein: The concave angle of the concave feature is between 15-150°; The distance between two adjacent primary structures is 1 nm-100 μm. Preferably, the distance between two adjacent primary structures is 0.3 μm-10 μm.
5. The super hydrophilic absorbent core according to claim 1, wherein: The zero-order structure is one of the inner surface groove of the shell plate of the heat spreader when the super hydrophilic wick is used in the heat spreader, the surface of the micro-groove type wick structure, the surface of the foam metal type wick structure, and the surface of the metal mesh type wick structure.
6. The super hydrophilic absorbent core according to claim 1, wherein: The material of the primary structure is different from the material of the secondary structure; preferably, the material of the primary structure is copper or nickel, and the material of the secondary structure is molybdenum or tungsten; more preferably, the material of the primary structure is nickel, and the material of the secondary structure is molybdenum.
7. The method for preparing the super hydrophilic liquid absorbent core according to any one of claims 1 to 6, characterized in that: The steps include: (1) First deposition: using the material of the primary structure as a deposition material and the zero-order structure as a working electrode, depositing a primary structure having a rod-shaped or pointed cone-shaped microstructure on the surface of the zero-order structure; (2) Second deposition: Using the sample obtained by the first deposition as the working electrode, electro-deposit the secondary structure with a microstructure having a rounded shape on the top of the primary structure.
8. The method for preparing a super hydrophilic liquid-absorbing core as claimed in claim 7, characterized in that: The process conditions of the first deposition and the second deposition are independently: Current density is 0.5-300mA·cm -2 Preferably, the current density is 5-150 mA·cm -2 ; The electrodeposition time is 1s-90min, preferably, the electrodeposition time is 30s-30min; The electrodeposition temperature is 0-150°C, preferably, the electrodeposition temperature is 25-100°C.
9. A heat spreader, characterized in that: The invention comprises an upper shell plate, a lower shell plate, an upper liquid absorbent core, a lower liquid absorbent core and a liquid injection hole; the upper shell plate and the lower shell plate are connected to each other to form a closed steam chamber, the liquid injection hole is connected to the steam chamber, the steam chamber is filled with working liquid through the liquid injection hole, the upper liquid absorbent core is arranged in the inner surface groove of the upper shell plate, the lower liquid absorbent core is arranged in the inner surface groove of the lower shell plate, and the upper liquid absorbent core and / or the lower liquid absorbent core are the super hydrophilic liquid absorbent cores according to any one of claims 1 to 6.
10. A method for preparing a vapor chamber according to claim 9, characterized in that: The steps include: (1) preparing an upper shell plate and a lower shell plate having grooves on the inner surface; (2) forming an upper liquid wick and a lower liquid wick in the inner surface grooves of the upper shell plate and the lower shell plate respectively; (3) connecting the upper shell plate and the lower shell plate to form a closed steam chamber and evacuating the chamber; preferably, the vacuum degree in the steam chamber is maintained at 0.01-5000 Pa, preferably, the vacuum degree is 0.1-1000 Pa; (4) Inject working liquid through the liquid injection hole and perform sealing and packaging to obtain the heat spreader.
